Analysis of D-Wave Topologies with k-Hop-Based Graph Metrics - Csaba Biró; Gábor Kusper (Quantum Reports, 2025)
In this paper, we present a graph-based analysis of the topology of D-Wave quantum computers, focusing on the Pegasus, Chimera, and Zephyr architectures. We investigate these topologies under different parameter settings using k-hop-based graph metrics. Each of these architectures comprises distinct subgraphs in which qubits are interconnected according to specific patterns dictated by their implementation. Our study pursues two primary objectives. First, we analyze the structural properties of the Chimera, Pegasus, and Zephyr topologies, examining their scalability and connectivity characteristics. Second, we evaluate the behavior of graph-based density and redundancy metrics within these architectures. The inherent symmetries of these quantum hardware designs provide a unique opportunity to systematically assess the effectiveness of these metrics across varying connectivity patterns. By leveraging these symmetries, our findings not only enhance the understanding of these topological structures but also offer deeper insights into the reliability and applicability of the proposed metrics in the broader context of quantum hardware design.